2007
DOI: 10.1529/biophysj.106.102087
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Dimerization of Proteins from the Epidermal Growth Factor Receptor Family by Single Wavelength Fluorescence Cross-Correlation Spectroscopy

Abstract: Single wavelength fluorescence cross-correlation spectroscopy (SW-FCCS), introduced to study biomolecular interactions, has recently been reported to monitor enzyme activity by using a newly developed fluorescent protein variant together with cyan fluorescent protein. Here, for the first time to our knowledge, SW-FCCS is applied to detect interactions between membrane receptors in vivo by using the widely used enhanced green fluorescent protein and monomeric red fluorescent protein. The biological system studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
138
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 157 publications
(161 citation statements)
references
References 56 publications
21
138
2
Order By: Relevance
“…The normalized dimer fraction of EGFR was 57% determined by SW-FCCS and DC-FCCS (both at the apical surfaces), and 65% by quasi PIE-FCCS (apical) and imaging FCCS (basal). The normalized values are an estimate of the actual dimer fraction obtained and are comparable with our previous study on EGFR (19). On the other hand, we have observed significant cell-to-cell variability, which was especially obvious from the imaging FCCS experiments.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The normalized dimer fraction of EGFR was 57% determined by SW-FCCS and DC-FCCS (both at the apical surfaces), and 65% by quasi PIE-FCCS (apical) and imaging FCCS (basal). The normalized values are an estimate of the actual dimer fraction obtained and are comparable with our previous study on EGFR (19). On the other hand, we have observed significant cell-to-cell variability, which was especially obvious from the imaging FCCS experiments.…”
Section: Discussionsupporting
confidence: 87%
“…Nagy et al (18) observed preformed dimers only at high expression levels of EGFR of ~600,000 receptors per cell. In contrast to that, in our previous study, we found dimerization to be independent of receptor expression levels in the range from 20,000 to 260,000 copies per cell (19). According to single particle tracking studies of EGFR, the receptor forms transient dimers in the absence of EGF (20)(21)(22); on the other hand, results of Tao and Maruyama (23) indicate that EGFR dimers are already formed in the endoplasmic reticulum, which would suggest a much more stable association.…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations